The India-Pakistan nuclear relationship : theories of deterrence and international relations - Sridharan, Eswaran; International Relations Theory and South Asia (Project) (New Delhi : Routledge, 2007)
Contributed articles presented earlier at two conferences.
Introduction: Subcontinental perspectives on deterrence theory, international relations theory and South Asia / E. Sridharan -- International relations theory and the India-Pakistan conflict / E. Sridharan -- Conceptualizing nuclear deterrence: Pakistan's posture / Rasul Bakhsh Rais -- South Asia: the irrelevance of classical nuclear deterrence theory / Bharat Karnad -- International relations theory and minimum deterrence / Rajesh M. Basrur -- Deterrence and nuclear use: doctrines in South Asia / Rifaat Hussain -- The stability-instability paradox: a less than perfect explanation / Varun Sahni -- Operation Vijay and Ooperation Parakram: the voctory of theory? / Waheguru Pal Singh Sidhu -- Theories of deterrence and nuclear deterrence in the subcontinent / Arvind Kumar -- The threat of unintended use of nuclear weapons in South Asia / Rajesh Rajagopalan -- The China factor in South Asia's nuclear deterrence / Swaran Singh.
Based on presentations at conferences in New Delhi, 2002-2006; results of International Relations Theory and South Asia (Project).
Includes bibliographical references and index.
Keywords: Nuclear arms control -- India -- Congresses; Nuclear arms control -- Pakistan -- Congresses; Deterrence (Strategy) -- Congresses; India -- Foreign relations -- Pakistan -- Congresses; Pakistan -- Foreign relations -- India -- Congresses